Accumulation of phytoene, a colorless carotenoid by inhibition of phytoene desaturase (PDS) gene in Dunaliella salina V-101. (October 2017) - Srinivasan, Ramachandran; Babu, S.; Gothandam, K.M.
Highlights: Successfully, we developed genetically modified phytoene-producing Dunaliella cells. Phenotypes with RNAi construct showed significant amount of phytoene. PDS-silenced Dunaliella cells were able to accumulate phytoene up to 108 µg/100 mg DW. Phytoene-accumulating Dunaliella cells were sensitive to high light conditions. Abstract: The aim of this work was to study the accumulation of phytoene in Dunaliella salina V-101 by down-regulating its phytoene desaturase (PDS) gene expression using RNA interference and Antisense technology. RNAi and antisense constructs were introduced into the Dunaliella cells by Agrobacterium-mediated transformation. Among thirty-two transformants, six showed positive down-regulation of PDS expression with RNAi construct and five positive transformants were obtained using antisense construct. Characterization of PDS suppression was carried out using semi-quantitative RT-PCR and quantitative determination of phytoene as well as other carotenoids by HPLC. Both the RNAi and antisense lines showed a significant decrease in the expression levels of phytoene desaturase and carotenoid content compared to wild type cells. The RNAi line #5 showed maximum Phytoene content (108.34 ± 22.34 µg/100 mg DCW) compared to other transgenic lines. These phytoene-accumulating phenotypes exhibited slower growth rates and were found to be sensitive to high light conditions.